Procession, pilgrimage and protest : a historical study of the Qadiriyya-Nasiriyya and Islamic movement in Nigeria, public religiosity in Northern Nigeria, 1952-2021 - Shehu, Abdullahi Hamisu (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.